SOIL QUALITY MONITORING TECHNOLOGY WITH IOT SENSORS IN NORWAY - Emine Yildiz; Baran Akbulut; Sevda Kara (Techno Agriculturae Studium of Research, 2025)
Internet of Things (IoT)-based soil quality monitoring technology presents new opportunities in sustainable agricultural management, especially in countries with extreme climatic conditions such as Norway. This study aims to evaluate the effectiveness of the use of IoT sensors in monitoring soil quality in real-time and its impact on agricultural productivity. A quasi-experimental research design was used by comparing a group that used IoT sensors and a control group that used traditional methods. The results show that the use of IoT improves the stability of soil moisture, temperature, pH, and nutrient levels, as well as reduces the waste of water and fertilizer. Farmers who used this technology reported a 15% increase in productivity compared to the control group. In conclusion, IoT technology has proven to be effective in improving land management efficiency and supporting sustainable agriculture, although infrastructure-related challenges still need to be addressed.